PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON PADA PELAJARAN SENI RUPA DI KELAS IV SDS PANCA BUDI MEDAN - Shabina Dinisyah Fajar, Natasya; Afriadi, Putra; Winara, Winara; Wahyu Purnomo, Try; Mustika Aulia, Sri (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
This study aims to determine the validity, practicality, and effectiveness of powtoon-based learning media in fine arts lessons in grade IV of SDS Panca Budi Medan. The learning media developed uses the ADDIE development model which includes analysis, design, development, implementation, and evaluation, especially material for drawing sketches of flora and fauna for grade IV students in the even semester of the 2024/2025 school year. A total of 20 grade IV students were involved as research subjects, along with two experts to test the validity of the media and one teacher to test the practicality of learning media in fine arts subjects in accordance with the independent curriculum. The validation results from the material experts showed a high score, namely 89 out of 110 scores with a percentage of 89%, while media design experts gave a score of 68 out of a maximum score of 75 with a percentage of 90.6%. Teachers also gave a high score on the practicality test with a score of 54 out of a total of 60, resulting in a percentage of 90%, where all aspects, such as appearance, presentation, material, and language, obtained the categories of "Very Feasible" and "Very Valid". Further evaluation showed a significant increase in student learning outcomes, as seen from the comparison of pre-test and post-test scores, where the pre-test score was 60 and the post-test score increased to 85.25, recording an increase of 25.25. ABSTRAK Penelitian ini bertujuan untuk mengetahui validitas, praktikalitas, dan efektivitas media pembelajaran berbasis powtoon pada pelajaran seni rupa di kelas IV SDS Panca Budi Medan. Media pembelajaran yang dikembangkan menggunakan model pengembangan ADDIE yang meliputi analisis, desain, pengembangan, implementasi, dan evaluasi, khususnya materi menggambar sketsa flora dan fauna bagi peserta didik kelas IV pada semester genap tahun ajaran 2024/2025. Sebanyak 20 peserta didik kelas IV terlibat sebagai subjek penelitian, bersama dengan dua ahli untuk menguji validitas media dan satu guru untuk menguji praktikalitas media pembelajaran dalam mata pelajaran seni rupa sesuai dengan kurikulum merdeka. Hasil validasi dari ahli materi menunjukkan skor tinggi, yaitu 89 dari skor 110 dengan persentase 89%, sementara ahli desain media memberikan skor 68 dari skor 75 maksimal dengan persentase 90,6%. guru juga memberikan penilaian tinggi terhadap uji praktikalitas dengan skor 54 dari total 60, menghasilkan persentase 90%, di mana semua aspek, seperti tampilan, penyajian, materi, dan bahasa, memperoleh kategori “Sangat Layak” dan “Sangat Valid”. Evaluasi lebih lanjut menunjukkan peningkatan signifikan dalam hasil belajar siswa, terlihat dari perbandingan skor pre-test dan post-test, dimana skor pre-test adalah 60 dan skor post-test meningkat menjadi85.25, mencatat peningkatan sebesar 25.25. Kata Kunci: Media Pembelajaran, Powtoon, Menggambar Sketsa